Moderate-intensity endurance training has higher effects suppression of oxidative stress secretion than strength training in obese students - Gigih Siantoro; Dwi Cahyo Kartiko; Muhammad Muhammad; Yanyong Phanpheng; Bayu Agung Pramono; I Dewa Made Aryananda Wijaya Kusuma; Yanuar Alfan Triardhana; Bhekti Lestari; Fajar Eka Samudra; Adi Pranoto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The objective of this research is to establish the impact of endurance training of moderate intensity and resistance exercises on the mitigation of oxidative stress in students with obesity. The research engaged a cohort of 30 female students, characterized by obesity, with an age average of 22.30±1.92 years and a Body Mass Index (BMI) averaging 31.77±2.72 kg/m2. These participants were randomly allocated into three distinct groups: the control group (CN, n=10), the group undergoing endurance training (ET, n=10), and the group subjected to strength training (ST, n=10). The intervention involving endurance training was executed at an intensity level of 60-70% HRmax, with each training session lasting between 40 to 60 minutes. Whereas, the strength training regimen was implemented with a load intensity of 60-70% 1RM, 4-6 sets, and 12-15 repetitions for each set. The intervention was administered with a regularity of three times per week for four weeks. Data collection was carried out by taking blood samples before and 24 hours after the last intervention—analysis of MDA levels utilizing the TBARs technique served as an indicator of oxidative stress. The technique employed for data analysis was the ANOVA test, then continued with the LSD post hoc test with a significant level (p≤0.05). The results showed that the average pre-MDA levels in CN, ET, and ST were (31.07±5.97, 32.12±8.91, and 31.36±8.52 ng/mL) respectively p=0.953. The mean post-MDA levels in CN, ET, and ST were (32.14±11.46, 15.21±8.01, and 22.02±7.33 ng/mL) respectively p=0.001. The mean delta MDA levels in CN, ET, and ST were (1.08±14.83, -16.91±9.68, and -9.34±7.51 ng/mL) respectively p=0.005. The average changes in MDA levels in CN, ET, and ST were (9.09±48.42, -51.71±24.77, and - 27.85±25.31 %) respectively p=0.002. Our findings revealed that both the endurance and strength training interventions resulted in a reduction of oxidative stress, as evidenced by the observed decrease in MDA levels following the training sessions. However, endurance training intervention has a higher effect on suppressing the secretion of oxidative stress than strength training in obese students.